ANALISIS USAHA PENANGKAPAN IKAN TUNA (thunnus sp.) DENGAN MENGGUNAKAN ALAT TANGKAP PANCING TONDA DI DESA AMPERA KABUPATEN ALOR PROVINSI NUSA TENGGARA TIMUR - Efrin A. Dollu; Raymundus Lobato Nua (Politeknik Pertanian Negeri Kupang, 2018)
Antioxidants are substances that can protect the body from various degenerative diseases caused by free radicals by neutralizing them. Plants that contain antioxidants, chemotaxonomically are characterized by chemical compounds derived from phenolics. One type of plant containing phenolic compounds is Soursop (Annona muricata L). This plant is one type of plant from Alor Island, East Nusa Tenggara, which has never been reported before. In this study, phytochemical screening and the antioxidant activity of Soursop leaf (Annona muricata L) using the DPPH method will be conducted. The results showed that the class of compounds contained in soursop leaves (Annona muricata L.) is a class of alkaloid and flavonoid compounds. Soursop leaves (Annona muricata L.) have weak antioxidant activity compared to Vitamin C, with IC50 values of soursop leaves of 292,727 mg / L and vitamin C of 117,140 mg / L but still, have the potential as antioxidants .